Relación entre los ingresos y los gastos de la Municipalidad Provincial de Maynas, periodo 2018 – 2022 - Paima Flores, Juan Romel (2024)
The municipalities have the purpose of ensuring the political representation of residents and promoting and conducting the socio-economic development of their constituency. Under this premise, this thesis was carried out, which aims to determine the relationship between the execution of income of the Provincial Municipality of Maynas in the execution of the expenses accrued by the financing source Directly Collected Resources, in the period 2018 – 2022. It is So the following Quantitative type research, Correlational level and Non[1]Experimental design was carried out. The research concludes that there is a linear relationship between the Income Earned and the Expenses Earned of the Provincial Municipality of Maynas, during the aforementioned five-year period. Likewise, the value of the Correlation coefficient (r) was 0.99566223, being a value very close to 1. Likewise, the Coefficient of Determination (R2) was 0.99134327, also close to 1; Therefore, there is a relationship and determination between Expenses (dependent variable) and Income (independent variable). In this sense, according to the regression analysis that was carried out and having the positive value of the parameter (b_1) ̂, the direct relationship between the Income and Expenses of the Provincial Municipality of Maynas during the analysis period is determined, that is , as the independent variable (income) increases, the dependent variable (expenses) increases.